Unravelling the interaction of piperlongumine with the nucleotide-binding domain of hsp70: A spectroscopic and in silico study - Povinelli, Ana Paula Ribeiro [UNESP]; Zazeri, Gabriel [UNESP]; Jones, Alan M.; Cornélio, Marinônio Lopes [UNESP] (MDPI, 2021)
Piperlongumine (PPL) is an alkaloid extracted from several pepper species that exhibits anti-inflammatory and anti-carcinogenic properties. Nevertheless, the molecular mode of action of PPL that confers such powerful pharmacological properties remains unknown. From this perspec-tive, spectroscopic methods aided by computational modeling were employed to characterize the interaction between PPL and nucleotide-binding domain of heat shock protein 70 (NBD/HSP70), which is involved in the pathogenesis of several diseases. Steady-state fluorescence spectroscopy along with time-resolved fluorescence revealed the complex formation based on a static quenching mechanism. Van’t Hoff analyses showed that the binding of PPL toward NBD is driven by equivalent contributions of entropic and enthalpic factors. Furthermore, IDF and Scatchard methods applied to fluorescence intensities determined two cooperative binding sites with Kb of (6.3 ± 0.2) × 104 M−1. Circular dichroism determined the thermal stability of the NBD domain and showed that PPL caused minor changes in the protein secondary structure. Computational simulations elucidated the mi-croenvironment of these interactions, showing that the binding sites are composed mainly of polar amino acids and the predominant interaction of PPL with NBD is Van der Waals in nature.
Keywords: Circular dichroism; Fluorescence spectroscopy; Heat shock protein; HSP70; Molecular docking; Molecular dynamics; Molecular mechanics Poisson–Boltzmann surface area; Nucleotide-binding domain; Piperlongumine